Domination criticism and freedom criticism on flood news in online media from a Foucauldian view - Christantyawati, Nevrettia; Izzati, Yuyun Wahyu; Dayanti, Liestianingsih Dwi (Faculty of Social and Political Science, Universitas Airlangga, 2024)
This article discusses the issue of flood disaster polemics in online media using McKerrow's critical rhetorical theory analysis, with the main aim of getting closer to discourse formations that have not been discussed in previous research on political interest contestation. This research uses Fairclough's critical discourse analysis method to reveal flood news articles from 2019-2021 on Tirto.id. Meanwhile, the Foucauldian perspective in this study is used as a review of McKerrow's critical rhetoric to analyze power, right and truth. Furthermore, this triangulation is explained in two criticisms, namely, criticism of domination and freedom in the online media Tirto.id in reporting on the flood. This study found that in terms of power, Tirto.id discusses criticism of power as a struggle for power in the social status of the upper and lower middle classes. Dominance tends to appear in social disparities and discrepancies in the effects of development on poor communities and the surrounding ecosystem. In terms of rights, Tirto.id discusses demands for ecological justice for lower middle class society. Finally, in terms of truth, the discourse about flood victims includes the lower classes as a result of land grabbing. This study concludes that criticism of domination shows that the government is not very serious about the concept of ecological justice for all groups. Criticism of freedom shows that Tirto.id expresses satire that floods are only suffered by poor people, not rich people.